Use of Commercial Microwave Links (CMLs) in estimating rainfall in Kenya - CGIAR Platform for Big Data in Agriculture (2019)
We developed an algorithm which can process the raw CMLs data and generate quantitative precipitation estimates at any given point in space. We support the reliability of this approach and show the advantages of this approach compared with rain gauges and CHIRPS using real data in Kenya.